Induction of Growth Factor‐receptor and Metalloproteinase Genes by Epidermal Growth Factor and/or Transforming Growth Factor‐α in Human Gastric Carcinoma Cell Line MKN‐28 - Yoshida, Kazuhiro (Jpn J Cancer Res, 1990)
We examined the effects of epidermal growth factor (EGF) and transforming growth factor‐α (TGF‐α) on EGF receptor (EGFR) phosphorylation and the expression of mRNAs for oncogenes, growth factors, their receptors and metalloproteinase genes by MKN‐28 gastric carcinoma cells which express EGF, TGF‐α and EGFR genes. Both EGF and TGF‐α stimulated EGFR phosphorylation. EGF and TGF‐α induced FOS, MYC and ERBB‐2 oncogene expression. Interestingly, EGF increased the expression of mRNAs for TGF‐α and EGFR. On the other hand, TGF‐α increased TGF‐α mRNA but decreased the expression of mRNAs for EGFR and TGF‐β. Furthermore, mRNAs for interstitial collagenase, stromelysin and procollagen type I genes were also enhanced after treatment with EGF and TGF‐α. These results indicate that EGF and TGF‐α successively evoke cascade phenomena which favor tumor progression, invasion and extracellular matrix formation, acting as autocrine growth regulators for gastric carcinomas.